The Effect on White Incomes of Discrimination in Employment - Bergmann, Barbara R. (Journal of Political Economy, 1971)
Discrimination concentrates Negroes into certain occupations while virtually excluding them from others. In the occupations to which Negroes are relegated, marginal productivity may be lowered by the enforced abundance of supply. A model embodying this "crowding" hypothesis is used to estimate the effects on white incomes of a reduction in discrimination. Whites with only an elementary education might have a once-for-all loss on the order of 10 percent; on all other whites and on national income the effect is estimated to be trivial. Formulations by Becker and Thurow concerning Negro marginal productivity and wages are criticized.